Identificação dos componentes do óleo essencial de laranja (Citrus sinensis L. Osbeck) e proposição de procedimentos industriais para a obtenção de produtos diferenciados - Tita, Marcelo Luiz (2011)
Brazilian exports of orange essential oil are responsible for moving approximately seventy-four million dollars, representing a significant portion of Brazilian business, and deserve the attention from the companies involved in this business. There was interest by the company (Cutrale) to conduct this research, due to the low number of papers found in the literature to promote the study with orange essential oil distillation facility at the industrial level. Thus, this work was aimed to study the essential oil of orange in its composition, and establish by vacuum distillation an industrial scale, of a system for preparing a product with sensory profile that was not available in the market. For that, we used statistical tools to deal with the results of chromatographic analysis of GC/MS, and sensory analysis to characterize the products obtained. The distillation was carried out in a distillery plant with about 1730kg of orange essential oil. It was the necessary the proper adjustment of the equipment and then the product was distilled, and several fractions were collected. The procedure was performed in two different set-ups. The first one involved low heating and low distilling flow, and the second higher heating and distilling flow. The originated fractions from both procedures were analyzed by GC/MS and their profile, were compared using PCA. Three samples were chosen for the sensory tests after the analysis by PCA. The tests revealed some sensory acceptability, either positive or negative of fractions of the juice when compared with the positive control (standard juice). This suggests that the testers do not have the taste for this type of product. Compared with a collection of samples of customers from abroad, received/analyzed by the company, these fractions are very similar, implying that there is possible that the samples we obtained may be of interest for international market.